Particulate monitoring, modeling, and management: natural sources, long-range transport, and emission control options: a case study of Cyprus - Kleanthous, Savvas; Savvides, Chrysanthos; Christofides, Ioannis; Themistocleous, Kyriacos; Achilleos, Constantia; Demetriadou, Chrystalla; Christodoulides, Paul; Douros, Ioannis; Moussiopoulos, Nicolas S.; Panayiotou, Charalambos; Charalambous, Gregoris; Fedra, Kurt; et al. (My University, 2013)
The LIFE+ Project PM3: Particulate Monitoring, Modeling, Management is coordinated by the Department of Labour Inspection in Cyprus and funded in part by LIFE+ Environment Policy & Governance. The project aims at the analysis of dust emissions, transport, and control options for Cyprus, as well as at the identification of “natural” contributions (Directive 2008/50/EC). The ultimate objective is to provide inputs for the design of a dust management plan to improve compliance to EC Directives and minimise impacts to human health and environment. This paper presents a short analysis of historical monitoring data and their patterns as well as a description of a dynamic dust entrainment model. The pyrogenic PM10 emissions combined with the wind driven emissions, are subject to a two phase non-linear multi-criteria emission control optimization procedure. The resulting emission scenarios with an hourly resolution provide input to the Comprehensive Air quality Model with extensions (CAMx) 3D fate and transport model, implemented for the 4,800 km master domain and embedded subdomains (270 km around the island of Cyprus and embedded smaller city domains of up to 30 km down to street canyon modeling). The models test the feasibility of candidate emission control solutions over a range of weather conditions. Model generated patterns of local emissions and long-range transport are discussed compared with the monitoring data, remote sensing (MODIS derived AOT), and the chemical analysis of dust samples.
Keywords: Natural Dust; Emission Modeling; Wind Erosion; Operational Forecasts; Nested Grid; Cascading Models; Emission Control Optimization; LIFE+ PM3